Penilaian Autentik Mata Pelajaran Pai Pada Kurikulum Merdeka Di SMAN 1 Sangatta Selatan - Sarwinda Rohmadani; Sulistia Wahyuningsih; Anjani Putri Belawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Even though authentic assessment has existed since the education unit curriculum, its implementation has not always been perfect. In addition, the independent curriculum places a strong emphasis on helping students develop their moral character. The term "authentic assessment" describes evaluation techniques that are intended to reflect a student's abilities in authentic or real-world situations.Data collection uses primary and secondary sources. Primary sources include interview observations, while secondary sources include books, journals and scientific articles. Data analysis uses descriptive-analytics including critical analysis, critical interpretation, and drawing conclusions. The aim of this research is to find out how authentic assessment is in the independent curriculum at State High School 1 very south. This approach helps students see connections between different areas of study and develop a more holistic understanding of knowledge. Then the independent curriculum also emphasizes character development and positive values ​​in students. Authentic Assessment refers to an evaluation method designed to reflect a student's abilities in a real-life context or real-world situation. This authentic assessment aims to determine students' understanding, application, knowledge, skills and attitudes outside the formal learning environment at school. Cognitive assessment in Islamic Religious Education subjects aims to measure the extent of students' ability to understand Islamic concepts and principles and students' ability to implement these skills in everyday life. Assessment Objectives Determining the objectives of this written exam will help subject teachers in framing questions that are related and appropriate to the student competencies they wish to measure.